2003
DOI: 10.1177/074193250302400103
|View full text |Cite
|
Sign up to set email alerts
|

Children Placed at Risk for Learning and Behavioral Difficulties

Abstract: Over the past 2 decades, a substantial knowledge base has accumulated about the fundamentals of young children's learning difficulties and behavioral problems. This information provides educators with powerful and practical information about how to identify children in need of intervention and how to ensure successful school experiences for all learners. In addition, a growing body of research is beginning to shed light on how to effectively incorporate empirically supported approaches into daily practices. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(36 citation statements)
references
References 46 publications
1
35
0
Order By: Relevance
“…Lower-income, lower working-memory span, and ADHD children, and, in one study, boys (who often have poorer inhibitory control than girls [ 8 ]) generally show the most EF improvement from any program. Early EF training is thus an excellent candidate for leveling the playing field and reducing the achievement gap (48) between more- and less-advantaged children. EFs predict later academic performance (3), so as go EFs, so goes school readiness and academic achievement.…”
Section: What Lessons Can Be Learned About What Aids Ef Development Imentioning
confidence: 99%
“…Lower-income, lower working-memory span, and ADHD children, and, in one study, boys (who often have poorer inhibitory control than girls [ 8 ]) generally show the most EF improvement from any program. Early EF training is thus an excellent candidate for leveling the playing field and reducing the achievement gap (48) between more- and less-advantaged children. EFs predict later academic performance (3), so as go EFs, so goes school readiness and academic achievement.…”
Section: What Lessons Can Be Learned About What Aids Ef Development Imentioning
confidence: 99%
“…How the underlying factors of academic and social functioning are related is not yet fully established; however, researchers have established the prevalence of social functioning deficits among students with learning difficulties or poor academic performance (Cornwall & Bawden, 1992;Hinshaw, 1992;O'Shaughnessy, Lane, Gresham, & Beebe-Frankenberger, 2003;Vaughn, McIntosh, & Spencer-Rowe, 1991). Other research has indicated that for students with poor social skills, the likelihood of experiencing peer rejection is greater (Haager & Vaughn, 1995;Vaughn, Elbaum, & Schumm, 1996), and interventions to improve rejection status have been less than successful (Vaughn, McIntosh, & Spencer-Rowe, 1991).…”
mentioning
confidence: 97%
“…Young lower-income children have disproportionately poor EFs (13,14). They fall progressively farther behind in school each year (15).…”
Section: Significancementioning
confidence: 99%